(untitled) - Rogers, Bruce (Princeton, New Jersey, 1996)
This book offers step-by-step program that teaches you critical test-taking techniques, helps you polish the language skills needed for the exam, and generally makes you a smarter test-taker. The main body of the book is divided into three sections: Listening comprehension; Structure and Written expression; Reading comprehension.
Keywords: English language,English language,English language,Test of english as a foreign language; Examinations,Study guides,Study and teaching,Textbooks for foreign speakers,Study guides